Boosting Lean Electrolyte Lithium–Sulfur Battery Performance with Transition Metals: A Comprehensive Review - Pan, Hui; Cheng, Zhibin; Zhou, Zhenyu; Xie, Sijie; Zhang, Wei; Han, Ning; Guo, Wei; Fransaer, Jan; Luo, Jiangshui; Cabot, Andreu; Wübbenhorst, Michael (Nano-Micro Letters, 2023)
Lithium–sulfur (Li–S) batteries have received widespread attention, and lean electrolyte Li–S batteries have attracted additional interest because of their higher energy densities. This review systematically analyzes the effect of the electrolyte-to-sulfur (E/S) ratios on battery energy density and the challenges for sulfur reduction reactions (SRR) under lean electrolyte conditions. Accordingly, we review the use of various polar transition metal sulfur hosts as corresponding solutions to facilitate SRR kinetics at low E/S ratios (< 10 µL mg−1), and the strengths and limitations of different transition metal compounds are presented and discussed from a fundamental perspective. Subsequently, three promising strategies for sulfur hosts that act as anchors and catalysts are proposed to boost lean electrolyte Li–S battery performance. Finally, an outlook is provided to guide future research on high energy density Li–S batteries. Highlights: 1 This review systematically analyzes the effect of the electrolyte-to-sulfur ratios on battery energy density and the challenges for sulfur reduction reactions under lean electrolyte conditions. 2 The strengths and limitations of different transition metal compounds are systematically presented and discussed from a fundamental perspective. 3 Three promising strategies for sulfur hosts that act as anchors and catalysts are proposed to boost lean electrolyte Li–S battery performance.